1918
DOI: 10.1093/infdis/22.6.580
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies on Bacterium Abortus and Related Bacteria: II. A Comparison of Bacterium Abortus with Bacterium Bronchisepticus and with the Organism which Causes Malta Fever

Abstract: The similarity between Bacterium bronchisepticus and Bacterium abortus in their growth on potato, and in their inability to attack sugars has been pointed out by Smith.' So far as the writer is aware, no further attention has been called to the similarity between the two organisms. From a biologic standpoint the resemblance is of interest; and since, as Mcfiowan" has shown, Bact. bronchisepticus causes epizootics among laboratory animals, and during an epizootic may inhabit the organs of normal animals, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
7

Year Published

1919
1919
1949
1949

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(20 citation statements)
references
References 0 publications
0
13
0
7
Order By: Relevance
“…These investigations suggested that there was some relationship between the organism discovered by Bruce in 1887 and that first described by Bang ten years later, though hitherto they had been considered to be entirely distinct. This suspected relationship was confirmed by Evans (9) in Washington who, in 1918, showed that on morphological and serological grounds the two were practically indistinguishable. This work was confirmed by Meyer and Shaw (10) and by Khaled(ii).…”
mentioning
confidence: 83%
“…These investigations suggested that there was some relationship between the organism discovered by Bruce in 1887 and that first described by Bang ten years later, though hitherto they had been considered to be entirely distinct. This suspected relationship was confirmed by Evans (9) in Washington who, in 1918, showed that on morphological and serological grounds the two were practically indistinguishable. This work was confirmed by Meyer and Shaw (10) and by Khaled(ii).…”
mentioning
confidence: 83%
“…The patient was treated with 1 Gm. of streptomycin and 90 grains (about 6 Gm.) of sulfa- diazine per day for nine days.…”
Section: Report Of Casementioning
confidence: 99%
“…Hartford, Conn. INCE the work of Evans (1918) proved the close relationship between Bact. abortus and Bact.…”
mentioning
confidence: 95%